2003
DOI: 10.1200/jco.2003.12.037
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Interleukin-6 Soluble Receptor and Transforming Growth Factor Beta1 Improves a Preoperative Nomogram for Predicting Biochemical Progression in Patients With Clinically Localized Prostate Cancer

Abstract: We found that pretreatment plasma levels of IL6SR and TGF-beta1 improved the ability to predict biochemical progression by a prognostically substantial margin. A nomogram including the pretreatment levels of these molecular markers, along with standard clinical markers, has been developed and internally validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(110 citation statements)
references
References 24 publications
2
105
1
2
Order By: Relevance
“…This approach has been previously reported by other authors for the prediction of a positive biopsy outcome 32 or the risk of biochemical failure subsequent to radical prostatectomy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…This approach has been previously reported by other authors for the prediction of a positive biopsy outcome 32 or the risk of biochemical failure subsequent to radical prostatectomy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…When Kattan et al added interleukin-6 soluble receptor and TGFb to their nomogram, clinical stage lost its significance in predicting recurrence (27) in multivariate analysis. Recently, Yegnasubramanian et al showed in a subgroup of their study population analysis that CpG island hypermethylation of PTGS2 predicted for increased risk of recurrence following a radical prostatectomy, whereas pathologic stage lost its significance as well (28).…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, platelet-free plasma levels of transforming growth factor b 1 (TGF-b 1 ) and interleukin-6 soluble receptor, which have been reported to be markedly elevated in patients with distant metastases from PCa, significantly enhanced prediction of BCR over the standard Kattan pretreatment nomogram (concordance index of 0.75 vs. 0.83 for a model supplemented by TGF-b 1 and interleukin-6 receptor). 25 Measurements of prostate-specific tissue kallikreins such as multiple PSA-forms and hK2 in blood have been shown to improve early detection and staging of PCa. 11,12,26 However, there are no previous data reported whether these measurements may enhance the predictive accuracy of the standard pretreatment model to assess risk for BCR.…”
Section: Discussionmentioning
confidence: 99%